Chronic kidney disease as a catalyst for cerebral microbleeds: understanding the underlying mechanisms and treatment approaches - Yang, Jia; Chen, Xuezhi; Cao, Xianming; Yang, Hui; Liu, Peiwen; Yin, Xiaoping; Zhang, Xiaorong; Chen, Zhiying (Frontiers in Medicine, 2025)
Cerebral microbleeds (CMBs) are tiny deposits of blood degradation products in the brain that appear as small, low-signal lesions on magnetic resonance imaging paramagnetic susceptibility sequences. They are common forms of the cerebral small-vessel diseases and are thought to be associated with serious consequences such as cognitive decline and increased risk of stroke. Chronic kidney disease (CKD) is a chronic disease in which renal impairment lasts for more than 3 months and is often accompanied by pathophysiologic changes such as inflammation, abnormal vascular endothelial function, and increased oxidative stress. It has been found that chronic renal insufficiency can induce the onset, development, and aggravation of cognitive impairment of CMBs, which may be caused by hypertension, inflammation and immune response, vascular lesions, blood–brain barrier damage, vitamin D deficiency, and so on. Therefore, it is essential to study the mechanism of cerebral microbleeds induced by chronic kidney disease to prevent the occurrence, development, treatment, and prognosis of stroke and related events in patients in the future. This article summarizes the definition, epidemiological investigation, pathophysiological mechanism, correlation, and treatment status of CMBs and CKD.